Morality as a predictor of loneliness: a cross-cultural study - J. Jordaan; A. le Roux (AOSIS, 2004)
Loneliness is currently regarded as one of the most common and prevalent problems experienced by adolescents, and it is also observed as a painful, unpleasant and negative experience. South African adolescents also have to face and cope with this predicament daily. The main objective of this study was to establish the perception of adolescents of different cultures regarding loneliness and morality and to investigate the relationship between them. It was also determined which of the independent variables, namely morality, gender, age, mother tongue and ethnicity, contributed significantly to the prediction of loneliness. A total of 714 adolescents from three different secondary schools in the greater Bloemfontein area between the ages of 13 and 17 were selected. Adolescents were used because they are increasingly being confronted with moral issues and because loneliness occurs more commonly during adolescence. The focus was on three ethnic groups, namely Coloured, black and white. Three different questionnaires, namely the Le Roux Loneliness Scale, the Morally Debatable Behaviours Scale and a biographical questionnaire were completed to obtain the necessary data.